Strategi Pendidik dalam Membentuk Life Skill Peserta Didik Sekolah Dasar - Andra Umarsyah, Yori; Luthvi Azizah, Alif; Kembar Habibi, Roy; Destini, Frida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the learning phenomenon in Indonesia, which requires educators to develop students’ life skills as preparation for facing life challenges. Curriculum demands and societal changes encourage educators to integrate personal and social skills into the learning process. This condition is also evident at SD Negeri 2 Metro Pusat, where learning has been directed toward fostering students’ life skills, particularly personal and social competencies. The objectives of this study are to identify educators’ strategies in developing students’ life skills, to describe the impacts of these strategies, and to analyze the supporting and inhibiting factors in their implementation at SD Negeri 2 Metro Pusat. This research employs a qualitative approach with a phenomenological design. Data collection techniques include interviews, observations, and documentation, while data validity is ensured through method and source triangulation. The data sources consist of the principal, third- and fourth-grade teachers, and third- and fourth-grade students. The results show that educators implement life skill development through active learning strategies, flexible teaching methods, and their roles as facilitators and mentors. These strategies have a positive impact on students’ self-awareness, social attitudes, thinking skills, self-confidence, and life readiness. Supporting factors include school policies, a conducive learning environment, and parental support, while inhibiting factors include limited time and facilities. It can be concluded that active learning strategies supported by the school effectively optimize the development of students’ personal and social life skills.